Parental Factors Associated with Child Post-traumatic Stress Following Injury: A Consideration of Intervention Targets - Wise, Anna E.; Delahanty, Douglas L. (Frontiers in Psychology, 2017)
Posttraumatic stress disorder (PTSD) symptoms are relatively common following pediatric traumatic injury and are related to poor long-term child outcomes. However, due to concerns regarding the efficacy of early child preventive interventions, and difficulty intervening with injured and medicated children soon after the event, it is not feasible to provide early psychological interventions to children exposed to traumatic injury. Parental PTSD symptoms (PTSS) and reactions to the child’s traumatic injury impact child outcomes and provide potential targets for early intervention to reduce child symptom development without involving the child. The authors conducted a review of the literature using Psychoinfo and Pubmed research databases (publication years = 1990-2017) and identified 65 published studies relevant to the topic of the review. The present review considers parent factors (parenting styles, parental post-traumatic pathology (PTS), adaptive and maladaptive coping strategies, and communication regarding the traumatic injury) and their impact on child PTS. We focus specifically on factors amenable to intervention. We further review moderators of these relationships (e.g., child age and gender, parent gender) and conclude that it is unlikely that a one-size-fits-all approach to treatment will be successful. Rather, it is necessary to consider the age and gender of parent child dyads in designing and providing targeted interventions to families following the traumatic injury of a child.